PENGARUH SUBSTRAT YANG BERBEDA TERHADAP PERTUMBUHAN RUMPUT LAUT SARGASUM SP HASIL PRODUKSI SPORA - A. Wawu; Nikodemus Dahoklory; Ridwan Tuboku (Jurnal Akuatik, 2018)
Abstract - The aim of this study to know the growth of sparger of seaweed Sargasum sp on different substrate and which substrate spores of seaweed Sargasum sp can grow optimally. The method used in this research is experimental field using descriptive analysis in the from of quality and quantitative using three treatments on polybag medium is treatment A sand of 75% sand, and mud 25%, treatment B mud of 75% mud and sand 25%, treatment C sandy mud of 50% sand and 50% mud excuted at BBIP Tablolong, districts Kupang Barat, district Kupang. The results showed that sand substrate had more optimal growth compared to mud and muddy sand. Keywords : Substrate, Spore growth, Seaweed Sargasum sp.